Pola terapi dan outcome therapy pasien penyakit ginjal kronik di Rumah Sakit Ansari Saleh Banjarmasin tahun 2023 - Sofia, Sofia; Sari, Okta Muthia; Putra, Aditya Maulana Perdana (Universitas Mataram, 2025)
Chronic kidney disease is a permanent disease that occurs when the body is unable to maintain the balance of fluids and electrolytes, leading to reduced kidney function. This study quantifies the distribution of therapy profiles among patients with chronic kidney disease, taking into account drug classes, names, doses, and methods of administration. The percentages are calculated based on doctors' statements. This descriptive research used total population sampling as a method for data collection. A total of 55 medical records met the research criteria. The therapy profile that was used most frequently, with a proportion of 13.60%, was the vitamin and mineral group. The medicine name AminefronÂ® accounted for 8.45% of the results. The prescribed dose was 3x2 capsules per day. The oral route represented the highest percentage of usage, at 55.67%. The doctor's declaration indicated that the percentage of patients who improved was 52.73%, while 38.18% remained sick and 9.09% unfortunately died.